2009
DOI: 10.1111/j.1574-6968.2009.01610.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus tianmuensissp. nov., isolated from soil in Tianmu Mountain national natural reserve, Hangzhou, China

Abstract: In a project aiming to isolate strains with the ability to produce nonribosomal peptides, a gram-negative, endospore-forming, rod-shaped strain, designated B5(T), was isolated from a soil sample collected from Tianmu Mountain national natural reserve in Hangzhou, China. Strain B5(T) contained meso-diaminopimelic acid in the cell wall peptidoglycan. The major cellular fatty acids were anteiso-C(15:0) and iso-C(15:0). The DNA G+C content was 42.5 mol%. The phylogenetic analysis based on 16S rRNA gene sequence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The 16S rRNA gene was amplified using two universal primers as described by Wu et al (2007). PCR amplification and DNA sequencing were conducted using the method of Wen et al (2009). The 16S rRNA gene sequence obtained was compared with the corresponding reference sequences retrieved from GenBank databases by blast search.…”
Section: Methodsmentioning
confidence: 99%
“…The 16S rRNA gene was amplified using two universal primers as described by Wu et al (2007). PCR amplification and DNA sequencing were conducted using the method of Wen et al (2009). The 16S rRNA gene sequence obtained was compared with the corresponding reference sequences retrieved from GenBank databases by blast search.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining isolates of the genus Bacillus were isolated from the superficial horizon of seamount station 6 and were respectively assigned to B. tianmuensis (CS 6067) (54) and B. barbaricus / B. arsenicus complex (CS 6054, 603, 6060, 6055 and CS 6052). These two species were characterized by their resistance to a high concentration of arsenic (45).…”
Section: Resultsmentioning
confidence: 99%
“…These two species were characterized by their resistance to a high concentration of arsenic (45). Wen et al (54) demonstrated that, within the genus Bacillus , the highest 16S rRNA sequence similarity was found between B. barbaricus and B. tianmuensis . In our study, the high phylogenetic relationship between these two species was confirmed by their segregation into the same cluster (Fig.…”
Section: Resultsmentioning
confidence: 99%